Bioactive phenols in leaves of Forsythia species - Sedlák, É.; Borsodi, L.; Boldizsár, E.; Preininger, É.; László, M.; Szőke, É.; Gyurján, I. (International Journal of Horticultural Science, 2008)
Nowadays a number of lignans (arctigenin, matairesinol, pinoresinol and phillygenin) have come to the fore in research due to their various biological activities. In this paper the accumulation of these constituents in leaf extracts of Forsythia plants (F. intermedia, F. ovata 'Robusta’ and `Tetragold', F. suspensa, F. viridissima) was quantified using a new isolation method, supercritical CO2 fluid extraction. The total phenolic and flavonoid contents, the antioxidant capacity and the aglycone lignan profile were determined in leaf extracts of Forsythia species. Within the phenols, the flavonoids were only present in small quantities, but the amount of aglycone lignans was extremely high. F. ovata `Robusta' had the highest total lignan content (103.8 mg/g) of all the Forsythia species. The main lignan in this species is arctigenin, which normally makes up about 60% of the total lignan content, but in the case of F. ovata `Robusta' this value was 96.1%. Since this arctigenin content is outstanding compared to that of other Forsythia species, it could be promising to develop a fermentation technology for the production of this natural compound.